Measuring exposure to bullying and harassment in health professional students in a clinical workplace environment: Evaluating the psychometric properties of the clinical workplace learning NAQ-R scale. (2nd July 2020) - Smith-Han, Kelby; Collins, Emma; Asil, Mustafa; Blakey, Althea Gamble; Anderson, Lynley; Berryman, Elizabeth; Wilkinson, Tim J.
Abstract: Background: Instruments that measure exposure to bullying and harassment of students learning in a clinical workplace environment (CWE) that contain validity evidence are scarce. The aim of this study was to develop such a measure and provide some validity evidence for its use. Method: We took an instrument for detecting bullying of employees in the workplace, called the Negative Acts Questionnaire – Revised (NAQ-R). Items on the NAQ-R were adapted to align with our context of health professional students learning in a CWE and added two new factors of sexual and ethnic harassment. This new instrument, named the Clinical Workplace Learning NAQ-R, was distributed to 540 medical and nursing undergraduate students and we undertook a Confirmatory Factor Analysis (CFA) to investigate its construct validity and factorial structure. Results: The results provided support for the construct validity and factorial structure of the new scale comprising five factors: workplace learning-related bullying (WLRB), person-related bullying (PRB), physically intimidating bullying (PIB), sexual harassment (SH), and ethnic harassment (EH). The reliability estimates for all factors ranged from 0.79 to 0.94. Conclusion: This study provides a tool to measure the exposure to bullying and harassment in health professional students learning in a CWE.